FORMULATION AND DEVELOPMENT OF MULTILAYER AND MONOLITHIC EXTENDED RELEASE MATRIX TABLETS OF ALFUZOSIN HCL - Devi.K, Jyothshna; B, Pavan Kumar.; Reddy. B, Venkateswara; Sindhuri, Manubolu; Madhavi, Pichika (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: In present investigation an attempt has been made to increase therapeutic efficacy, reduce frequency of administration and improve patient compliance, by developing extended release monolithic and multilayered tablets of Alfuzosin hydrochloride. Methods: Extended release matrix tablets of Alfuzosin were developed by using different drug and polymer ratio with guar gum, Hydroxypropylmethylcellulose, xanthan gum as matrix formers. All lubricated formulations were compressed by wet granulation method. Results: Compressed tablets were evaluated for uniformity of weight, content of active ingredient, friability, hardness, thickness, invitro dissolution. All the formulation showed compliance with Pharmacopoeial standards. In vitro release studies indicated that matrix multilayer tablets prepared by wet granulation with various proportions of polymer mixtures failed to control the drug release for extended period of time. Controlled delivery of Alfuzosin could be achieved in F8, F9 and to a lesser extent F7 tablet formulations which released 67percent, 86percent,and 90percent of drug, respectively, at the end of 20th hr in 0.01N HCl. Conclusion: Among these monolithic matrix tablets F9 prepared with guar gum-HPMC-xanthan gum mixture in 1ration11ration4 shown comparable drug release profiles at 1st and 20th h as 18percent and 86percent as that of the innovator Xatral Drug release kinetics indicated that drug release was best explained by Higuchi as these plots showed the highest linearity r x r = 0.9979. Keywords: Alfuzosin, matrix multilayer, xanthan gum, Methocel, extended release.